The Use Of Songs As A Tool For Language Education In Multilingual Populations - Budianto, Suhartawan; Tobing, Victor Maroli Tua L; Brumadyadisty, Garry; Huda, Nuril; Budianto, Sony Piously (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. In Indonesia, children are often exposed to multiple languages from an early age. English, being the dominant foreign language, poses challenges in learning due to the limited vocabulary among students. Previous studies suggest that traditional methods might not be sufficiently effective in improving English proficiency, especially in vocabulary acquisition. This study aims to evaluate the effectiveness of integrating songs into English language education for elementary students, focusing on vocabulary enhancement and overall language skills improvement. An experimental research design was employed involving 80 elementary students from the first grade, divided into control and experimental groups. The intervention consisted of using English children's songs in the language learning process, with assessments conducted through pre-tests and post-tests to measure vocabulary acquisition and retention. The experimental group, exposed to the song-based learning method, showed significant improvements in English vocabulary compared to the control group. Post-test results indicated a higher average score in vocabulary tests for the experimental group. Incorporating songs into language education can significantly enhance vocabulary learning and retention among young learners. This method provides a conducive learning environment and fosters better engagement with the language.Keywords: English proficiency, language learning, multiligualism, song-based education